2018
DOI: 10.1002/ar.23747
|View full text |Cite
|
Sign up to set email alerts
|

Scaling of Primate Forearm Muscle Architecture as It Relates to Locomotion and Posture

Abstract: It has been previously proposed that distal humerus morphology may reflect the locomotor pattern and substrate preferred by different primates. However, relationships between these behaviors and the morphological capabilities of muscles originating on these osteological structures have not been fully explored. Here, we present data about forearm muscle architecture in a sample of 44 primate species (N = 55 specimens): 9 strepsirrhines, 15 platyrrhines, and 20 catarrhines. The sample includes all major locomoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
50
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 33 publications
(50 reference statements)
6
50
1
Order By: Relevance
“…However, as FL is proportional to shortening velocity, longer fibers shorten at greater velocity and therefore are capable of greater power generation, difference in FL between species have been linked to differences in function (Lieber & Ward, ; Rose, Nudds, & Codd, ). It has been suggested that positive scaling of FL is often associated with muscles for which there is a strong functional signal for particular behavior (i.e., differing diets, different locomotor styles) (Leischner et al, ). As such, we might expect that if larger Quenda are digging to a greater extent that FL should have increased with positive allometry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as FL is proportional to shortening velocity, longer fibers shorten at greater velocity and therefore are capable of greater power generation, difference in FL between species have been linked to differences in function (Lieber & Ward, ; Rose, Nudds, & Codd, ). It has been suggested that positive scaling of FL is often associated with muscles for which there is a strong functional signal for particular behavior (i.e., differing diets, different locomotor styles) (Leischner et al, ). As such, we might expect that if larger Quenda are digging to a greater extent that FL should have increased with positive allometry.…”
Section: Discussionmentioning
confidence: 99%
“…This trade‐off is common, for example, in jaw muscles (Hartstone‐Rose, Perry, & Morrow, ) and hindlimbs (Marchi et al, ) as larger animals have different functional pressures than smaller species. The positive allometry in PCSA of the primate's forelimbs combined with isometry in FL, suggest that larger species rely on stronger forearms while smaller species have relatively faster and more flexible forearms (Leischner et al, ). A similar case was made for interspecific variation in the forelimb muscles of felids (Cuff et al, ); however, after a phylogenetic correction was performed, these results were not significant.…”
Section: Discussionmentioning
confidence: 99%
“…Leischner et al. ), or the collection of manual pressure distributions during gripping behaviors (e.g. Williams‐Hatala et al.…”
Section: Introductionmentioning
confidence: 99%
“…Eight taxa (including P. potto ) were dissected for the purposes of this study; the remaining data are derived from a previously published dataset (Leischner et al. ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation